Pedagogical Grammar Approach to English Skill Development: A Case Study at Diniyyah Pekanbaru - Novitri, Safriyani; Astuti, Missi Tri; Yulianto, Yulianto; Jayanti, Nonik Widiya; Auliana, Ratu Ganisa (Universitas Pahlawan Tuanku Tambusai, 2025)
Effective English communication is essential for students at the Islamic Institute of Diniyyah Pekanbaru, yet traditional teaching methods have fallen short in developing practical language skills. This study explores the use of a pedagogical grammar approach that integrates grammar instruction with communicative activities to enhance English proficiency. Using a descriptive qualitative method, data were collected from 20 students through observations, interviews, and document analysis. Findings show that this approach boosts student motivation, participation, and practical language use. The study offers valuable insights into grammar-integrated instruction in Islamic education, highlighting its potential for long-term language improvement.